CPA Examination: Accounting Practice. - Chamberlain, John H. (The Accounting Review, 1965)
The article presents problems prepared by the Board of Examiners of the American Institute of Certified Public Accountants (CPA) that were presented as the second half of the CPA examination in accounting practice on May 13, 1965. The first problem is related to the sale of an apartment house the accounting records for which are maintained on the cash basis method. For the quarterly audit, the information available includes that the apartment building and land were purchased for $223,000. The building was being depreciated over a 40-year life by the straight-line method for the purposes of both reporting and income taxes. Accumulated depreciation after three-and-a-half years was $17,500. No depreciation has been recorded on the books after that. The contract of sale stated that the price for the land on which the building was built was $25,000. The purchase money mortgage payments are $1,000 per month plus accrued interest. The students were required to prepare the adjusting journal entries to record the sale on books, and to compute the taxable capital gain that can be expected on the installment sale method.